Stretchable HfO₂-based resistive switching memory using the wavy structured design - Wang, Ming (2022)
In this letter, we report a stretchable HfO2-based resistive switching memory device utilizing the wavy structured strategy. The fabricated Cu/HfO2/Au device shows reliable and reversible resistive switching behaviors up to a stretching strain of 20%. After being released, the reproducible memory characteristics of the device can still be maintained. The statistical resistive switching parameters under various stretching strains in the range from 0% to 20% are counted, which exhibit a large OFF/ON resistance ratio (103), low operation voltage (2 V), good endurance and retention (104s), demonstrating the good and reliable stretchable memory characteristics. Moreover, the device-to-device distributions are carried out in these stretched states, further validating the device robustness on stretching strains. Our results show a promising approach to achieve the stretchable memory by rendering inorganic-based resistive switching devices with the wavy structure, which extends rigid and brittle memory towards future highly flexible, even stretchable data storage and computing.